2014
DOI: 10.1139/cjfas-2013-0442
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the environmental context of recentDidymosphenia geminataproliferation in Gaspésie, Quebec, using paleolimnology

Abstract: Management authorities often perceive Didymosphenia geminata (didymo) as an invasive, nuisance diatom species that has been introduced to eastern Canada; however, observations from early 20th century diatom surveys challenge this characterization. We apply paleolimnological techniques to place recent didymo blooms from Gaspésie, Quebec, into historical and environmental context. Sedimentary diatom assemblages were examined from Lac Humqui (a headwater lake) and Lac au Saumon (a lake with an inflowing river cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Each species has its own environmental preferences, thus the environmental science Science from the Source diatom assemblage (the collection of species) is highly reflective of its surrounding environment. "Introduced" or "invasive" are problematic designations for microorganisms such as diatoms, including didymo 9 . It has been suggested that random dispersal (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Each species has its own environmental preferences, thus the environmental science Science from the Source diatom assemblage (the collection of species) is highly reflective of its surrounding environment. "Introduced" or "invasive" are problematic designations for microorganisms such as diatoms, including didymo 9 . It has been suggested that random dispersal (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the idea of an invasive diatom species is difficult to confirm, as absence of evidence is not evidence of absence 10,11 . Additionally, it is difficult to establish whether a species is truly absent using conventional sampling methods that may underestimate the presence of rare taxa 9,10,11 . Therefore, determining whether didymo (and other diatom species) can truly be considered "introduced" is challenging 9 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations